2015
DOI: 10.4314/gjds.v10i1-2.1
|View full text |Cite
|
Sign up to set email alerts
|

Economic Cost of Malaria Treatment under the Health Insurance Scheme in the Savelugu-Nanton District of Ghana

Abstract: The paper discusses the findings of a survey which explored the implications of access to health care by examining costs incurred by health insurance card holders in the Savelugu-Nanton District. Treatment for malaria, a disease that causes morbidity and mortality in Sub-Sahara Africa, US$ 46.20 (2009 prices). While indirect costs were disproportionately greater than direct costs, the study affirmed that health insurance generally insulate subscribers from monetary payments which in itself increases both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
3
1
Order By: Relevance
“…In spite of the concerns from beneficiaries, it can be stated that the project interventions were generally sustainable. This result disagrees with Zakaria (2011) who found that NGOs are unable to sustain their development interventions.…”
Section: Resultscontrasting
confidence: 86%
“…In spite of the concerns from beneficiaries, it can be stated that the project interventions were generally sustainable. This result disagrees with Zakaria (2011) who found that NGOs are unable to sustain their development interventions.…”
Section: Resultscontrasting
confidence: 86%
“…The average indirect cost (GH¢25.04/US$6.59) was 1.7 times higher than the direct cost (GH¢14.87/US$3.91). This is consistent with many findings where the indirect costs of malaria treatment were higher than the direct costs of treatment [11,15,33,37,38]. Therefore, efforts to improve access to health care and reduction of financial burden to households in the treatment of malaria should not only be directed to direct medical costs but also indirect costs.…”
Section: Discussionsupporting
confidence: 89%
“…The overall average cost of treating malaria in the Kassena Nankana District was estimated at US GH¢27.83/US$7.2. Though the cost of treatment is lower than malaria treatment cost estimated in other similar studies conducted in other parts of Ghana [11,33], this amount is still relatively high given that most of the respondents were from poor households. High treatment costs can prevent the poor from seeking care when they have a fever episode as well as impoverish households who seek care when they have an episode of fever [11,34].…”
Section: Discussionmentioning
confidence: 73%
“…This is much lower, compared to those of higher‐income countries such as Australia (US$516.46‐US$ 66 856.92) 10 and Malaysia (US$1716.47) 9 . To put the economic burden of the condition in local perspective, our reported average direct cost of paediatric maxillofacial fractures however is higher compared with that of Cholera (US$ 84.45), 21 Malaria (US$ 46.20), 22 and Meningitis (US$ 72.14) 23 in Ghana. The average annual household income in Ghana is equivalent to US$1,273 24 .…”
Section: Discussionmentioning
confidence: 98%